COX Inhibition Profiles and Molecular Docking Studies of the Lignan Hinokinin and Some Synthetic Derivatives. Issue 12 (1st August 2018) - Borges, Alexandre; Casoti, Rosana; e Silva, Marcio Luis Andrade; da Cunha, Nayane Larissa; da Rocha Pissurno, Ana Paula; Kawano, Daniel Fábio; da Silva de Laurentiz, Rosangela
Abstract: Encouraged by the anti‐inflammatory activity of hinokinin in vivo, which is also observed for the analogues dinitrohinokinin and diidrocubebin, herein we used in vitro and in silico methods to assess their selectivity profiles and predict their binding modes with Cyclooxygenases (COX‐1 and 2). The in vitro assays demonstrated dinitrohinokinin is about 13 times more selective for COX‐2 than for COX‐1, a similar profile observed for the drugs celecoxib (selective index ≈9) and meloxicam (selective index ≈11). Predictions of the binding modes suggested dinitrohinokinin interacts with COX‐2 very similarly to rofecoxib, exploring residues at the hydrophilic pocket of the enzyme that accessible to ligands only in this isoform. This lignan also interacts with COX‐1 in a similar mode to meloxicam, blocking the access of the substrate to the catalytic cleft. Therefore, dinitrohinokinin is a promising lead for the design of selective COX‐2 inhibitors. Abstract :